Regulation of cytochrome c oxidase activity by c-Src in osteoclasts - Miyazaki, Tsuyoshi (The Rockefeller University Press, 2003)
The function of the nonreceptor tyrosine kinase c-Src as a plasma membrane–associated molecular effector of a variety of extracellular stimuli is well known. Here, we show that c-Src is also present within mitochondria, where it phosphorylates cytochrome c oxidase (Cox). Deleting the c-src gene reduces Cox activity, and this inhibitory effect is restored by expressing exogenous c-Src. Furthermore, reducing endogenous Src kinase activity down-regulates Cox activity, whereas activating Src has the opposite effect. Src-induced Cox activity is required for normal function of cells that require high levels of ATP, such as mitochondria-rich osteoclasts. The peptide hormone calcitonin, which inhibits osteoclast function, also down-regulates Cox activity. Increasing Src kinase activity prevented the inhibitory effect of calcitonin on Cox activity and osteoclast function. These results suggest that c-Src plays a previously unrecognized role in maintaining cellular energy stores by activating Cox in mitochondria.